2006
DOI: 10.1530/eje.1.02081
|View full text |Cite
|
Sign up to set email alerts
|

Cybernetic principles in the systematic concept of hypothalamic feeding control

Abstract: Research on biological mechanisms of eating behavior and related disorders, such as obesity and anorexia nervosa, has become a large field of research in the last 15 years. With the discovery of peptides related to hypothalamic control of food intake (e.g. leptin and ghrelin) the search for the biological 'master key' of feeding control was renewed. As a result, mid-20th century biological concepts based on systematic and cybernetic thoughts fell into oblivion. This review highlights discoveries of hypothalami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…More generally, the array of arousal-related phenomena that is modulated by estrogens provides indirect evidence of the importance of estrogens to elementary arousal. In women, fMRI analysis has shown that the menstrual cycle modulates arousal circuitry (Goldstein, et al, 2005), and affects cognition (Resnick, et al, 1998;Swerdlow, et al, 1997), ingestive behavior (Fricke, et al, 2006), and sexual arousal (Diamond, et al, 1972;Stanislaw and Rice, 1988). These are supported by a growing body of studies in research animals regarding mood (i.e.…”
Section: Interpretative Issuesmentioning
confidence: 98%
“…More generally, the array of arousal-related phenomena that is modulated by estrogens provides indirect evidence of the importance of estrogens to elementary arousal. In women, fMRI analysis has shown that the menstrual cycle modulates arousal circuitry (Goldstein, et al, 2005), and affects cognition (Resnick, et al, 1998;Swerdlow, et al, 1997), ingestive behavior (Fricke, et al, 2006), and sexual arousal (Diamond, et al, 1972;Stanislaw and Rice, 1988). These are supported by a growing body of studies in research animals regarding mood (i.e.…”
Section: Interpretative Issuesmentioning
confidence: 98%
“…Most of the literature reviewed for this article provides a fairly closed and integrated model of regulation in which the biological system analysed (in rats or humans) and itsfor the most part labenvironment are presented as ontologically distinct. Nevertheless, in their analysis of the cybernetics of body weight regulation, Fricke et al (2006) examine the role of systems thinking in analysing the molecular aspects of homoeostatic control of food intake. Their conclusion is worth citing at length for it marks a clear break with the tenor of much of the literature on homoeostatic regulation:…”
Section: Feedback Models and Complex Systems In Changing Environmentsmentioning
confidence: 99%
“…Most of the literature reviewed for this article provides a fairly closed and integrated model of regulation in which the biological system analysed (in rats or humans) and its – for the most part lab – environment are presented as ontologically distinct. Nevertheless, in their analysis of the cybernetics of body weight regulation, Fricke et al (2006) examine the role of systems thinking in analysing the molecular aspects of homoeostatic control of food intake. Their conclusion is worth citing at length for it marks a clear break with the tenor of much of the literature on homoeostatic regulation:

The attribution of control elements to biological structures always contains the problem of semantic simplification, because the biological structure is reduced to a singular meaning.

…”
Section: Feedback Models and Complex Systems In Changing Environmentsmentioning
confidence: 99%
“…Therefore, feedback loops might be organized in chains, where elements are parts of different loops in different functions. (Fricke et al , 2006, p. 171)…”
Section: Feedback Models and Complex Systems In Changing Environmentsmentioning
confidence: 99%